Congenital posterior cervical spine malformation due to biallelic c.240‐4T>G RIPPLY2 variant: A discrete entity. Issue 6 (25th March 2020) - Serey‐Gaut, Margaux; Scala, Marcello; Reversade, Bruno; Ruaud, Lyse; Cabrol, Christelle; Musacchia, Francesco; Torella, Annalaura; Accogli, Andrea; Escande‐Beillard, Nathalie; Langlais, Jean; Piatelli, Gianluca; Consales, Alessandro; et al.
Abstract: The clinical and radiological spectrum of spondylocostal dysostosis syndromes encompasses distinctive costo‐vertebral anomalies. RIPPLY2 biallelic pathogenic variants were described in two distinct cervical spine malformation syndromes: Klippel–Feil syndrome and posterior cervical spine malformation. RIPPLY2 is involved in the determination of rostro‐caudal polarity and somite patterning during development. To date, only four cases have been reported. The current report aims at further delineating the posterior malformation in three new patients. Three patients from two unrelated families underwent clinical and radiological examination through X‐ray, 3D computed tomography and brain magnetic resonance imaging. After informed consent was obtained, family‐based whole exome sequencing (WES) was performed. Complex vertebral segmentation defects in the cervico‐thoracic spine were observed in all patients. WES led to the identification of the homozygous splicing variant c.240‐4T>G in all subjects. This variant is predicted to result in aberrant splicing of Exon 4. The current report highlights a subtype of cervical spine malformation with major atlo‐axoidal malformation compromising spinal cord integrity. This distinctive mutation‐specific pattern of malformation differs from Klippel–Feil syndrome and broadens the current classification, defining a sub‐type of RIPPLY2 ‐related skeletal disorder. Of note, the phenotype of one patient overlaps with oculo‐auriculo‐vertebral spectrum disorder.